Aerodynamic Optimisation of a Tandem Blade Centrifugal Compressor Through Parametric Analysis of Blade Angles and Count - Soylemez, Mustafa Erturk; Ozer, Salih (Mdpi, 2026)
This study advances the performance of a tandem-blade centrifugal compressor through a parametric Computational Fluid Dynamics (CFD) methodology integrated with Response Surface Methodology (RSM). Numerical simulations were executed by solving steady-state Reynolds-Averaged Navier-Stokes (RANS) equations utilising the Shear Stress Transport (SST) k-omega turbulence model on a validated structured hexahedral mesh. Local sensitivity analysis identified the hub outlet angle and hub inlet angle as the primary geometric parameters affecting pressure ratio and isentropic efficiency, respectively. Flow-field visualisations confirmed that the tandem configuration effectively re-energises the boundary layer, thereby reducing separation and enhancing pressure recovery. Using a Multi-Objective Genetic Algorithm (MOGA), an optimal blade design comprising 22 blades was determined, achieving a maximum isentropic efficiency of 95.23% and a total pressure ratio of 1.416. These findings provide valuable quantitative insights for the optimal design of tandem impellers and highlight the effectiveness of integrating CFD-based sensitivity analysis with multi-objective optimisation techniques.
Keywords: Centrifugal Compressor; Tandem Blade; Cfd Optimisation; Response Surface Methodology; Moga